Cytoreductive Surgery Combined with Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Metastasis from Colorectal Cancer - Yano, Hideaki (Clinics in Colon and Rectal Surgery, 2020)
Peritoneal metastasis from colorectal cancer (PM-CRC) is used to be considered a systemic and fatal condition; however, it has been growingly accepted that PM-CRC can still be local disease rather than systemic disease as analogous to liver or lung metastasis.Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is now considered an optimal treatment for PM-CRC with accumulating evidence. There is a good reason that CRS + HIPEC, widely accepted as a standard of care for pseudomyxoma peritonei (PMP), could be a viable option for PM-CRC given a similarity between PM-CRC and PMP.Recent years have also seen that modern systemic chemotherapy with or without molecular targeted agents can be effective for PM-CRC. It is possible that neoadjuvant or adjuvant chemotherapy combined with CRS + HIPEC could further improve outcomes.Patient selection, utilizing modern images and increasingly laparoscopy, is crucial. Particularly, diagnostic laparoscopy is likely to play a significant role in predicting the likelihood of achieving complete cytoreduction and assessing the peritoneal cancer index score.
Keywords: HIPEC; PCI; cytoreductive; carcinomatosis